Dipole coupling of a hole double quantum dot in germanium hut wire to a microwave resonator. (24th August 2020) - Xu, Gang; Li, Yan; Gao, Fei; Li, Hai-Ou; Liu, He; Wang, Ke; Cao, Gang; Wang, Ting; Zhang, Jian-Jun; Guo, Guang-Can; Guo, Guo-Ping
Abstract: The germanium (Ge) hut wire system has strong spin–orbit coupling, a long coherence time due to a very large heavy-light hole splitting, and the advantage of site-controlled large-scale hut wire positioning. These properties make the Ge hut wire a promising candidate for the realization of strong coupling of spin to superconducting resonators and scalability for multiple qubit coupling. We have coupled a reflection line resonator to a hole double quantum dot (DQD) formed in Ge hut wire. The amplitude and phase responses of the microwave resonator revealed that the charge stability diagrams of the DQD are in good agreement with those obtained from transport measurements. The DQD interdot tunneling rate is shown to be tunable from 6.2 GHz to 8.5 GHz, which demonstrates the ability to adjust the frequency detuning between the qubit and the resonator. Furthermore, we achieved a hole–resonator coupling strength of up to 15 MHz, with a charge qubit decoherence rate of 0.28 GHz. Meanwhile the hole spin–resonator coupling rate was estimated to be 3 MHz. These results suggest that holes of a DQD in a Ge hut wire are dipole coupled to microwave photons, potentially enabling tunable hole spin–photon interactions in Ge with an inherent spin–orbit coupling.